REFORMULASI PENGUATAN MAJELIS PERMUSYAWARATAN (MPR) DALAM PROSES IMPEACHMENT PRESIDEN DI INDONESIA - Mulyanto, Mulyanto (Faculty of Law, Universitas Sebelas Maret, 2012)
Abstract The purpose of this research is to arrange the model of People’s Consultative Assembly’s role strengthening formulation in the impeachment process of President/Vice-president in the Indonesian State Structure System. The model is based on the findings of a comprehensive comparative-study with an evaluative prescriptive approach. The research used an empirical research method with a qualitative approach. The research was conducted for one year. Its data consisted of primary and secondary ones. The data of the research were gathered through in-depth interview, questionnaire, focus discussion group, and library research. The results of the research show that the mechanisms of the impeachment of President/Vice-president in the history of Indonesia’s formerly prevailing Constitutions have differences. The model of Peoples’ Consultative Assembly’s role strengthening formulation in the impeachment process of President/Vice-president is manifested in the reformulation of the impeachment substances by improving the conceptualization of Peoples’ Consultative Assembly as an administrative confirmation institution. In addition, in term of impeachment procedure, the minimum quorum limit should be changed so that to conduct an impeachment of President/Vice-president is not more difficult than to conduct an amendment of the 1945 Constitution. People’s Consultative Assembly’s should implement the rule of law (constitution) rather than political supremacy as happened during this, so that the concept can be applied to State law. As a suggestion the People’s Consultative Assembly’s should make substantive and procedural reformulation of impeachment of President/Vice-president in the state system of Indonesia.